1995
DOI: 10.1182/blood.v86.12.4627.bloodjournal86124627
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of signaling events associated with activation of neutrophil superoxide anion production by eosinophil granule major basic protein

Abstract: This study was undertaken to identify the signaling events involved in activation of neutrophil superoxide anion (O2-) production by eosinophil granule major basic protein (MBP). MBP did not produce an immediate increase in the cytosolic free calcium concentration ([Ca2+]i), characteristic of phospholipase C activation, but did cause a gradual increase in [Ca2+]i in cytochalasin B-treated cells. Preincubation with 0.01 to 3 micrograms/mL pertussis toxin did not inhibit MBP-stimulated O2- production, and MBP di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…This highly charged cationic protein can induce epithelial mucus, prostaglandin and ion secretion (34,36,38,62), smooth muscle contraction (61), basophil histamine release (51), neutrophil oxidative burst (29), fibroblast IL-6 expression (54), and eosinophil and fibroblast IL-8 secretion (26,37). The mechanism by which MBP induces these host responses is not yet certain, but the rapid activation of tyrosine phosphorylation signaling by MBP (29) suggests the presence of a MBP receptor. In our present study, we have shown that MBP can induce transcriptional responses, providing further support for a MBP-related pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This highly charged cationic protein can induce epithelial mucus, prostaglandin and ion secretion (34,36,38,62), smooth muscle contraction (61), basophil histamine release (51), neutrophil oxidative burst (29), fibroblast IL-6 expression (54), and eosinophil and fibroblast IL-8 secretion (26,37). The mechanism by which MBP induces these host responses is not yet certain, but the rapid activation of tyrosine phosphorylation signaling by MBP (29) suggests the presence of a MBP receptor. In our present study, we have shown that MBP can induce transcriptional responses, providing further support for a MBP-related pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity toward helminthic parasites such as schistosomulae of Schistosoma mansoni (Butterworth 1984;Ackerman et al 1985;Gleich & Adolphson 1986) Cytotoxicity toward airway epithelium (Frigas et al 1980;Hastie et al 1987;Hisamatsu et al 1990;Furuta et al 2005) Bronchoconstriction and hyperresponsiveness on aerosolization in rats and monkeys (Gundel et al 1991;Coyle et al 1993;Uchida et al 1993) Platelet agonist (Rohrbach et al 1990) Activation of complement via classical and alternative pathways (Weiler et al 1992(Weiler et al , 1995) Antibacterial properties (Lehrer et al 1989) Activation of remodeling factors from epithelial cells (Pégorier et al 2006) Increased cutaneous vasopermeability (Davis et al 2003) Stimulation of signaling pathways and mediator release from mast cells, neutrophils and basophils (Zheutlin et al 1984;Haskell et al 1995;Page et al 1999;Shenoy et al 2003) ECP Ribonuclease activity (100 times less potent than EDN) (Slifman et al 1986) Toxicity toward helminthic parasites and mammalian epithelial cells (McLaren et al 1981;Ackerman et al 1985) Bactericidal properties (Lehrer et al 1989) Induction of Gordon phenomenon (Durack et al 1979;Fredens et al 1982) Promotion of mast cell degranulation (Zheutlin et al 1984) EDN Weakly toxic for parasites and mammalian cells (Ackerman et al 1985) Induction of Gordon phenomenon (Durack et al 1979) Antiviral activity in respiratory infection (Rosenberg & Domachowske 2001) EPO Toxic for mammalian cells and degradative toward connective tissue via ability to form hypohalous acids (Slungaard & Mahoney 1991;…”
Section: Mbpmentioning
confidence: 99%
“…Recent studies have demonstrated that eosinophils can also synthesize cytokines and chemokines, such as IL‐6, IL‐8, RANTES, and IL‐16(152157). Thus, eosinophils represent a source of cytokines that are chemoattractants for neutrophils and lymphocytes as well as eosinophils.…”
Section: Eosinophils Are Activated By Cytokines and Chemokinesmentioning
confidence: 99%